Bad dog and that Hollywood hoohah - Chatterton, Martin (New York : Scholastic, 2004)
Bad Dog has just three days to live before the City Pound for Unwanted Cannies puts him to sleep, unless he can show a big Hollywood agent that he is the right dog to appear in a big new action movie.
G5
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Motion pictures -- Production and direction -- Fiction; Hollywood (Los Angeles, Calif.) -- Fiction